Maze of deception : [a Clone Wars novel] - Hand, Elizabeth (New York : Scholastic, Inc., 2003)
"When he died in the first Clone War battle, Jango Fett left a fortune somewhere on the planet of Aargau. The bounty hunter Aurra Sing is the only person who knows where the fortune is. But Jango's son, Boba Fett, is the only person who can get to it..."
"Lucas Books."
Keywords: Star Wars fiction; Imaginary wars and battles -- Juvenile fiction